Health Human Resources Guidelines: Minimum Staffing Standards and Role Descriptions for Canadian Cystic Fibrosis Healthcare Teams - McIntosh, Ian D. (Can Respir J, 2016)
In cystic fibrosis clinics across Canada, the most common barrier that healthcare workers face when providing care to their patients is having too little time. The Health Human Resources Guidelines were developed to define specifically what amounts of time should be allocated for each discipline of cystic fibrosis clinical care and to provide a description of all the roles involved, reinforcing how these work together to provide comprehensive multidisciplinary care. With involvement from all cystic fibrosis clinics in Canada, through the use of a tailored survey, the Health Human Resources Guidelines are an exclusively Canadian document that has been developed for implementation across the country. The guidelines have been incorporated into a national Accreditation Site Visit program for use in evaluating and improving care across the country and have been distributed to all Canadian cystic fibrosis clinics. The guidelines provide hospital administrators with clear benchmarks for allocating personnel resources to the cystic fibrosis clinics hosted within their institutions.